Ibn Taymiyyah as an Islamic historian - Musa Tijani, Ibraheem; Islam, Arshad (IIUM Press, International Islamic University Malaysia, 2017)
This book highlights the historical views of Ibn Taymiyyah throughout his writings; with the aim of establishing whether he possesses authority on the historical issues he dealt with. The method used in this book, being an exploratory research, is to explore his intellectual background in the field and also his acquaintance with the various works and authors of this science. After which, his methods of criticizing historical narratives is analyzed to further show his consciousness of fabricated and false narratives attributed to historical incidents.